A Real-Time Optimal Route Computation for Public Transport System Using Web - Nalini, K.; Suneel, Sai; Sridevi, S. B. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
In this work describes web-map public transport enquiry system as described in this paper, gives a good example of providing bilingual information and public transport run in the form of interactive maps and texts, as well as real time derivation of optimal travelling routes for users in terms of multiple criteria, i.e., preferred mode, least changes, shortest travelling time, or lowest fare. This paper describes a research on The Flexible Bus Systems (FBS) using SMAC as a communication medium. The Flexible Bus System is a demand responsive transit (DRT) but it is more efficient and convenient in a sense that it entertains passengers demands and gives bus locations in real time. The real time synchronization of The Flexible Bus System makes it information rich and unique as compared to other DRTs. The Flexible Bus Systems is a system that can replace the Traditional Bus Systems with its flexibility and efficiency. This paper discusses the use of wireless technologies in The Flexible Bus Systems and how to make it more reliable using short range wireless technology SMAC protocol.